The Relationship between Sc Delivery with the Eracs Method and Asphyxia in Newborn Babies at Bunda Pengharapan Hospital, Merauke, South Papua - Frederika sondegau; Tety Ripursari; Riza Tsalatsatul mufida; Nita Dwi Astikasari (Journal of Health Science Community, 2024)
The SC ERACS method is a safer Caesarean delivery method with a faster recovery process than the Caesarean delivery process in general. SC ERACS allows the patient to move the body more quickly. That is, about two hours after a Caesarean section with minimal pain. This study aims to determine the relationship between ERACS SC method delivery and the incidence of asphyxia in newborns in the working area of ​​Bunda Pengharapan Hospital Merauke, South Papua. This research uses a research design Quantitative. The research method uses correlative descriptive with approach cross sectional. With technique sampling purposive A sample of 30 respondents was obtained, the independent variable (SC delivery ERACS method) and the dependent variable (Incidence of Asphyxia in newborns) using questionnaires and medical records. Statistical tests are used Chi-Square to find out the relationship between the two variables. The research results from 30 respondents almost all chose SC ERACS surgery, namely (80%), the majority of which were 24 respondents, with the incidence rate of newborn asphyxia being 17 babies, namely (56.7%) and there were 13 babies who did not experience asphyxia based on the results of the Chi statistical test. -Sguare where there is a significant correlation between birth by sc eracs method and the incidence of asphyxia in newborn babies. Analysis using the Chi-Square statistical test shows that the significance value is equal to 0.046 for the incidence of asphyxia and 0.001 for the type of operation with an error rate of 5%, meaning the p.value is smaller than 0.5, which means there is a relationship between the incidence of asphyxia and the type of SC ERACS. for ​​Bunda Pengharapan Hospital SPO SC ERACS revised and socialized the latest SPO, paying attention to the competency of the staff who will be given the task of receiving babies born SC both SC ERACS and non ERACS, ensuring that the baby receiving team is complete (SP.A Doctor, PERINATAL nurse/Midwife) in order to reduce incidence of asphyxia in newborns.